Of Whales and Savages: Reflections on Translating Louis Nicolas’ Histoire naturelle des Indes occidentales - Senior, Nancy (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThe Histoire naturelle des Indes occidentales by Louis Nicolas, an unpublished late seventeenth-century work, describes natural species in New France and many practices of native people. Translating it involves questions of language (words and expressions that have changed meaning), natural history (identifying species of plants, animals, birds and fish), and social relations. References to native people raise questions about how to deal with words such as sauvage and barbare, where the cognate word in English has different connotations from the French word.